Re-Evaluating the Bourgeoisie: A Parallel between Deirdre McCloskey and Sergio Ricossa - Alberto Mingardi (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
This paper compares Deirdre McCloskey's reading of the "bourgeois reevaluation" with Sergio Ricossa's. Italian economist Sergio Ricossa was – like McCloskey – schooled in the neoclassical, formalistic tradition, but in time drifted toward a more "Austrian" approach, as he was influenced by the work of F.A. Hayek. Like McCloskey, in a number of works Ricossa aimed to vindicate the bourgeoisie, placing what McCloskey would later call "the bourgeois deal" at the source of modern economic growth. Ricossa and McCloskey were not connected, nor friends. Yet they both arrived at re-evaluating the bourgeoisie, explicitly linking their liberalism to the historical role played by a specific class. This paper will look at their respective paths, which in some respects are parallel, and will show how their common appreciation of the Bourgeois Era went hand-in-hand with libertarianism as a political philosophy and with a strong appreciation of the Bourgeois Era in history.
Keywords: B15; B25; B31; B53; A11; B10; B12; 330; Economic History; Classical Liberalism; Deirdre McCloskey; Sergio Ricossa; Bourgeoisie